Mammographic density in relation to breast cancer recurrence and survival in women receiving neoadjuvant chemotherapy - Zdanowski, Anna; Sartor, Hanna; Feldt, Maria; Skarping, Ida (Frontiers in Oncology, 2023)
Objective The association between mammographic density (MD) and breast cancer (BC) recurrence and survival remains unclear. Patients receiving neoadjuvant chemotherapy (NACT) are in a vulnerable situation with the tumor within the breast during treatment. This study evaluated the association between MD and recurrence/survival in BC patients treated with NACT. Methods Patients with BC treated with NACT in Sweden (2005–2016) were retrospectively included (N=302). Associations between MD (Breast Imaging-Reporting and Data System (BI-RADS) 5th Edition) and recurrence-free/BC-specific survival at follow-up (Q1 2022) were addressed. Hazard ratios (HRs) for recurrence/BC-specific survival (BI-RADS a/b/c vs. d) were estimated using Cox regression analysis and adjusted for age, estrogen receptor, human epidermal growth factor receptor 2, axillary lymph node status, tumor size, and complete pathological response. Results A total of 86 recurrences and 64 deaths were recorded. The adjusted models showed that patients with BI-RADS d vs. BI-RADS a/b/c had an increased risk of recurrence (HR 1.96 (95% confidence interval (CI) 0.98–3.92)) and an increased risk of BC-specific death (HR 2.94 (95% CI 1.43–6.06)). Conclusion These findings raise questions regarding personalized follow-up for BC patients with high MD (BI-RADS d) pre-NACT. More extensive studies are required to confirm our findings.